Religious Culture as the Basis For Formation of Religious Behavior at MAN 1 Palembang - Zulhijra; Syarnubi (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2024)
J. Stanley's research concluded that the main aspects that determine success are honesty, high discipline, easy going, partner support, hard work, passion, leadership, competitive, and persuasive. In fact, the issue of moral decadence continues to grow. The parents still feel fear about the negative impact of globalization. The children are more easily influenced by negative moral values. As a basis for inculcating values and cultivating behavior, education should be illustrated the positive and negative impacts of globalization. The objectives of the study were to: analyze the create and developt of religious culture in MAN 1 Palembang, shape religious attitudes and behavior of the member of MAN 1 Palembang.The paradigm of this research are constructivism, a qualitative approach, a study research, and the data collection techniques are carried out by observation, interviews, and documentation. This research also using the stages of K Yin data analysis, they are: compiling, disassembling, reassembling, interpreting, concluding. The conclusion of this research is The creation of religious culture is formulated with the term PKP (Pencanangan visi misi, Kegiatan rutin, Program sekolah: Declaration of vision and mission, routine activities, school programs). From the declaration of the school's vision and mission, it was then implemented in routine activities and school programs: One Day One Juz, Halaqoh al-Qur'an, Clean Friday actions. The development of religious culture is implemented through a tradition of noble character. The findings of religious culture that shape the religious attitudes and behavior of school residents are formulated with 3M: (Menciptakan lingkungan kondusif, Mengaplikasikan keteladanan, Melaksanakan program ekstrakurikuler: Creating a conducive environment, applying exemplary, Implementing extracurricular programs).